The impact of religiosity, animosity, and ethnocentrism on american product purchase intention: Product and country image as a mediator / Mahmoud Odeh Eid Hamad - Mahmoud Odeh, Eid Hamad (2015)
This study aims initially to investigate the relationship among animosity, religiosity, and ethnocentrism in Saudi Arabia, as well as their impact on consumer purchases of foreign products. The second aim of this study is to assess both the individual and the collective impacts on the product image and country image of the U.S. on Saudi Arabian consumers' purchase intentions. The study examined the attitudes, perceptions, and belief structures of 530 Saudi Arabian consumers towards the U.S. as a country, along with their propensity to purchase U.S. made products. Data were collected in Saudi Arabia, which involved several steps of statistical analysis used to validate and test the hypotheses of the study. These include exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation modeling (SEM). The correlating variables of consumer ethnocentrism, consumer animosity and religiosity found to be mediated by product image, but did not demonstrate such a relationship with country image. This may be attributable to the prolonged hostility between the two countries (The U.S. and Saudi Arabia), which may have caused religiosity to influence animosity towards the U.S. Nevertheless, the choice of purchasing U.S. made products was not shaped through these variables. ii The study demonstrates that the governments of two countries maintain cordial relationships as reflected in their burgeoning defense cooperation and global trade; however, potential consumers from both countries have shown mutual hostility after the September 11 terrorist attacks in the U.S. The study also reveals the manner by which rich or poor products and country image relate with other variables. The results indicate a strong and significant inverse relationship between animosity, religiosity and ethnocentric feelings and the intention to buy U.S. made products. There is a mediating effect only between product image and consumer ethnocentrism, consumer animosity and religiosity, whereas country image does not yield any mediation. The results of the study reveal that Saudi Arabian consumers are ethnocentric; they hold animosity and a poor country image, but surprisingly, also hold a high product image. In brief, although the Saudi Arabian consumer level of religiosity, which can affect animosity and ethnocentrism, is influenced by country image, it can still lead to a lower consumption of foreign-made products. However, with Saudi Arabian consumers‟ perceptions towards the product itself, country image is rendered useless, and thus has no significant role to play. Irrespective of feelings held by locals towards the U.S., and regardless of the low perception held against the U.S, the choice to buy their products is unaltered. In fact, they are preferred over foreign-made products from other countries. This study is predicted to be of benefit to future managers and marketers in order to gain a competitive advantage in one of the world‟s most pertinent markets. By comprehending and analysing the manner in which cultural factors affect decision-making, as well as acquiring fruitful insights on how levels of religion, nationalism, and politics iii create a network of behavioral integration, individuals in the business sector equipped with a novel mindset can formulate effective strategies that cater differently the needs of different people. The examples in this study highlight how product image and country image stand apart among consumers who are able to distinguish between feelings from needs; and thinking about wanting and prejudices from desire Keywords: Animosity, Religiosity, Ethnocentrism, Product Image, Image Country United States (US), Saudi Arabia